Pathologic upstaging and survival outcomes for patients undergoing segmentectomy versus lobectomy in clinical stage T1cN0M0 non–small cell lung cancerCentral MessagePerspective - Ryan C. Jacobs, MD, MS; Erik E. Rabin, MD; Charles D. Logan, MD; Sandeep N. Bharadwaj, MD; Hee Chul Yang, MD; Raheem D. Bell, MD; Emily J. Cerier, MD; Chitaru Kurihara, MD; Kalvin C. Lung, MD; Diego M. Avella Patino, MD; Samuel S. Kim, MD; Ankit Bharat, MBBS (JTCVS Open)
Objectives: To assess the impact of the extent of surgical resection on overall survival in patients with clinical T1cN0M0 (cT1cN0M0) non–small cell lung cancer (NSCLC), with and without pathologic nodal upstaging (pN1+). Methods: The National Cancer Database (NCDB) was queried to identify patients with cT1cN0M0 NSCLC who underwent lobectomy or segmentectomy without receiving neoadjuvant therapy between 2010 and 2021. Bivariate analyses were performed to compare demographic and clinical characteristics across surgical groups. Propensity score matching was used to compare outcomes of segmentectomy versus lobectomy. Cox proportional hazard models and Kaplan-Meier survival estimates were used to assess the association of overall survival on the interaction between extent of resection and pathologic nodal upstaging. Results: A total of 22,945 patients were analyzed, including 21,875 (95.3%) who underwent lobectomy and 1070 (4.7%) who underwent segmentectomy. Pathologic nodal upstaging to pN1+ occurred in 14.5% of lobectomy cases and in 6.6% of segmentectomy cases. Propensity score–matched analysis revealed that patients undergoing segmentectomy had comparable overall survival to those undergoing lobectomy (hazard ratio [HR], 1.00; 95% confidence interval [CI], 0.86-1.16), and those undergoing segmentectomy with pN1+ had comparable overall survival to those undergoing lobectomy with pN1+ (HR, 1.04; 95% CI, 0.65-1.66). Conclusions: In patients with cT1cN0M0 NSCLC, overall survival outcomes are similar between segmentectomy recipients and lobectomy recipients, including those incidentally found to have pN1+, suggesting a potential role of lobe-preserving approaches. Additionally, completion lobectomy may not offer a survival benefit in cT1cN0M0 patients incidentally discovered to have pathologic N1 nodes.